An annotated bibliography of materials on Thailand written and/or published in the Philippines - Chety, Sida (1974)
This annotated bibliography includes classified and unclassified works - theses (undergraduate and graduate), dissertations, seminar and conference papers, investigation papers, articles in periodicals, and miscellaneous publications on Thailand which are produced and published in the Philippines and written by Thais, Filipinos, or other nationals in the Philippines. These are on different subject areas and cover the period from 1933 up to June 1973. Excluded, however, are articles from popular magazines and newspapers.